“Bilateral Ureteral Diffuse Large B-Cell Lymphoma” from the Diagnosis to the Management: A Unique Case to be Reported and Review of Literature - Elsawy, Amr A.; Rasha, Abouelkheir T.; Amira, Elhawary K. (Archives of Clinical and Medical Case Reports, 2019)
We are reporting a rare case of bilateral ureteral Non-Hodgkin's lymphoma. A 55-year-old male patient was presented with bilateral loin pain, oliguria and high serum creatinine (8 mg/dl). Non contrast computed tomography revealed bilateral hydroureteronephrosis down to bilateral upper lumbar ureteral soft tissue masses. Drainage of the kidneys by fixation of bilateral indwelling ureteral stents was done. Evaluation of the patient by magnetic resonance imaging revealed bilateral enhancing proximal ureteral lesions. Bilateral diagnostic ureteroscopy revealed bilateral fleshy lesions in the upper lumbar ureter from which was retrieved. The biopsy was positive for poorly differentiated urothelial carcinoma. The patient was managed by right nephroureterectomy. Histopathological evaluation of the radical specimen was highly suspicious for lymphoma. Immunohistochemistry analysis confirmed the presence of diffuse large B-cell lymphoma. The patient received three cycles of multi-agent chemotherapy. Complete remission of the left ureteral lesion was confirmed by magnetic resonance imaging and diagnostic ureteroscopy.